Idiopathic isolated clitoromegaly: A report of two cases - Copcu Ozgen; Sivrioglu Nazan; Aktas Alper; Copcu Eray; Oztan Yucel (BMC, 2004)
Abstract Background Clitoromegaly is a frequent congenital malformation, but acquired clitoral enlargement is relatively rare. Methods Two acquired clitoromegaly cases treated in Atatürk Training Hospital, Izmir, Turkey are presented. Results History from both patients revealed clitoromegaly over the last three years. Neither gynecological nor systemic abnormalities were detected in either patient. Karyotype analyses and hormonal tests were normal. Abdominal and gynaecological ultrasound did not show any cystic lesion or other abnormal finding. Computerized tomography scan of the adrenal glands was normal. Clitoroplasty with preservation of neurovascular pedicles was performed for the treatment of clitoromegaly. Conclusion The patients were diagnosed as "idiopathic isolated" clitoromegaly. To the best of our knowledge, there has been no detailed report about idiopathic clitoromegaly in the literature.